(untitled) (The Research of Medical Science Review, 2025)
Background: Melasma is a chronic pigmentation disorder with a significant effect on quality of life. Chemical peels are extensively employed as adjuvants to conventional depigmenting treatments in order to boost efficacy and response to treatment. The current study compares the safety and efficacy of 50% glycolic acid peel vs. modified Jessner peel (14% lactic acid, 14% salicylic acid, 8% citric acid) each employed as adjuvants to triple combination therapy for facial melasma. Objective: To assess and compare the clinical effectiveness, tolerability, patient satisfaction, and recurrence rates of glycolic acid and modified Jessner peels along with topical triple therapy in melasma patients. Methods: This prospective observational cohort study was conducted at the Dermatology Department of CMH Abbottabad from September 2024 to March 2025. A total of 60 patients with facial melasma were enrolled and equally divided into two groups. Group A was treated with 50% glycolic acid peel and Group B with modified Jessner peel, both given every second week for six sessions in combination with daily application of triple combination cream (hydroquinone 4%, tretinoin 0.05%, and fluocinolone acetonide 0.01%). Melasma Area and Severity Index (MASI) score was measured at baseline and every two weeks. Adverse effects and patient satisfaction were evaluated by standardized criteria. Recurrence was observed at 12 weeks post therapy. SPSS version 26 was used to analyze data. Results: A statistically significant decrease in MASI scores from baseline through week 12 was found in both treatment groups (p < 0.001). The glycolic acid group had a slightly greater mean reduction in MASI (9.0 vs 8.4). However, side effects such as erythema, peeling, and burning occurred more often in the glycolic group (p < 0.05). High patient satisfaction was observed in both groups, 80% in the glycolic and 73.3% in the Jessner group being satisfied. Recurrence at 12 weeks post therapy was less in the glycolic (13.3%) compared to the Jessner (23.3%) group. Conclusion: Glycolic acid and modified Jessner peels are both safe and effective adjuvants to triple combination therapy of melasma. Glycolic acid peel has slightly greater efficacy and less recurrence, while the modified Jessner peel has better tolerability. Choice of treatment should be individualized according to the patient's skin sensitivity and therapeutic objectives.